Evaluation of nutritional status (Nutritional Risk Screening-2002) of hospitalized inpatients and comparison with various variables - Ali Emrah Bıyıklı; Ezgi Toptaş Bıyıklı (Acta Medica Alanya)
Aim: This study aimed to evaluate the nutritional status of hospitalized patients according to Nutritional Risk Screening-2002 (NRS-2002) and to examine the effects of various variables on nutritional status.Methods: The sample of the cross-sectional study consisted of 469 inpatients reached by simple random sampling method. Data was collected from hospitalized patients with a survey form using face-to-face interview method between January and March 2024. Personal information and hospital stay characteristics form, NRS-2002 form was used in the survey used to collect data.Results: The average age of the patients included in the study was found to be 59.8±18.1 years. Of the patients, 51.4% were male and 48.6% were female. According to the total NRS-2002 score result, 410 (87.3%) of the patients were classified as no risk of malnutrition and 59 (12.6%) were classified as risk of malnutrition. No statistically significant difference was found between patients’ malnutrition risk and gender, education level, hospital diets, hospital clinics (p>0.05). However, a statistically significant difference was found between the malnutrition risk of the patients and their age, body mass index (BMI) and length of hospital stay (p<0.05).Conclusion: Nutrition screening tools should be applied more frequently to these patients, especially since the risk of malnutrition is higher in patients who are elderly, have a long hospital stay, and have a low BMI.